Implementing public relations strategies in digital nutrition communication: Evidence from MTATV - Bima Soultan Ilyas; Esfandani Peni Indreswari; Rahmat Wisudawanto (Societa: Journal of Society and Change, 2026)
The rapid growth of social media has encouraged broadcasting institutions to utilize Instagram as a communication medium for disseminating health information to the public. This study aims to analyze the public relations communication strategy employed by MTATV Surakarta in promoting the Saatnya Wanita Berbicara program, particularly the Sehat dan Gizi episode, through Instagram from the perspective of Rosady Ruslan's public relations strategy framework. This study employed a qualitative descriptive method with a case study approach, using observation, interviews, documentation, and Miles and Huberman's interactive data analysis. The findings indicate that MTATV's public relations department implemented operational, persuasive and educational, cooperative, coordinative and integrative, and social responsibility strategies in an integrated manner, thereby expanding the dissemination of information while enhancing public health education. The novelty of this study lies in its analysis of the implementation of public relations communication strategies within an Islamic broadcasting institution in utilizing Instagram as a medium for nutrition education through Rosady Ruslan's public relations strategy framework. Abstrak Perkembangan media sosial mendorong lembaga penyiaran memanfaatkan Instagram sebagai media komunikasi untuk menyebarluaskan informasi kesehatan kepada masyarakat. Penelitian ini bertujuan menganalisis strategi komunikasi humas MTATV Surakarta dalam menyosialisasikan program Saatnya Wanita Berbicara episode Sehat dan Gizi melalui Instagram berdasarkan perspektif Rosady Ruslan. Penelitian menggunakan metode deskriptif kualitatif dengan pendekatan studi kasus melalui observasi, wawancara, dokumentasi, dan analisis data interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa humas MTATV telah mengimplementasikan strategi operasional, persuasif dan edukatif, kerja sama, koordinatif dan integratif, serta tanggung jawab sosial secara terpadu sehingga mampu memperluas penyebaran informasi sekaligus meningkatkan edukasi kesehatan kepada masyarakat. Kebaruan penelitian ini terletak pada analisis implementasi strategi komunikasi humas media penyiaran berbasis dakwah dalam memanfaatkan Instagram sebagai media edukasi gizi melalui pendekatan strategi humas Rosady Ruslan.